(untitled) (The Peerian Journal, 2022)
The article describes that it is impossible the development of society without the development of science, in this sense our state pay attention to in the field of science in the context of science and social-political reform, spiritual renewal as in all countries of the world. Scientifically and practically defined the role of information technology in the development of science and technology, as well as the creation of effective mechanisms for stimulating research and innovation, the introduction of science and innovation achievements. Moreover, the role and significance of information technology in the development of scientific research in the field of technology was stated.